Analysing New York Times Opinion â€œIs America Becoming a Failed State?â€ Under the Perspective of Appraisal Framework: A Systemic Functional Linguistics Implementation - Pratama, Januari Rizki (Allure Journal, 2021)
Â The contestation of Americaâ€™s presidency in 2020 showed a very competitive and strict run. Both candidates provided arguments and attacked each other in public discussion rooms. However, it is a typical of a normal election where there will be always campaigns from the candidates to persuade and to gain publicâ€™s votes as much as possible. Therefore, the 2020 presidential election of America feels unusual compared to the previous. Besides it was conducted within the pandemic outbreak, the high tension of global conflict issues and internal social-economic problems of America caused the contestation becoming hotter and noteworthy. Regardless of its final result, it is really interesting to discuss the discourses appeared in the public room regarding the issue. New York Times, one of the leading media in USA provides the room for publics to participate in writing their opinion. This study tried to analyse a writing written in opinion column entitled â€œIs America Becoming a Failed State?â€ using appraisal system. The discourse was analysed in the three aspects of Whiteâ€™s appraisal framework namely attitude, graduation, and engagement. Under the scope of critical discourse analysis, this study aimed to elucidate the appraisal aspects found in the text regarding publicâ€™s opinion and its standing points to the issue. This study is a descriptive qualitative and the data were collected from an article in New York Times. The discussion was also connected to some external factors besides the three aspects mentioned such as political, economic, and socio-cultural factors.Â Â Â